Hyperforin and Miquelianin from St. Johnʼs Wort Attenuate Gene Expression in Neuronal Cells After Dexamethasone-Induced Stress - Verjee, Sheela; Weston, Anna; Kolb, Christiane; Kalbhenn-Aziz, Heba; Butterweck, Veronika (Planta Medica, 2018)
Dysregulation of the hypothalamic-pituitary-adrenal (HPA) axis plays an important part in the development of depressive symptoms. In this study, the effects of a commercial St. Johnʼs wort extract (STW3-VI), hyperforin, miquelianin, and the selective serotonin reuptake inhibitor citalopram on the expression of genes relevant to HPA axis function were investigated in human neuronal cells. SH-SY5Y cells were treated with STW3-VI (20 µg/mL), hyperforin (1 µM), miquelianin (10 µM), or citalopram (10 µM) in the presence of the glucocorticoid receptor agonist dexamethasone (DEX,10 µM) for 6 h and 48 h, respectively. Quantitative real-time polymerase chain reaction was used to determine the expression of FKBP5 (FK506 binding protein 51), CREB (cAMP responsive element binding protein), GRIK4 (glutamate ionotropic receptor kainate type subunit 4), VEGF (vascular endothelial growth factor), NET (norepinephrine transporter), and ARRB (β-arrestins), promising biomarkers of antidepressant therapy. Using DEX to mimic stress conditions, it was shown that the gene expression pattern of FKBP5, CREB, GRIK4, VEGF, NET, and ARRB2 in SH-SY5Y cells is time- and treatment-dependent. Most pronounced effects were observed for FKBP5: after 6 h of co-incubation, only STW3-VI could reverse the DEX-induced increase in FKBP5 expression, and after 48 h, citalopram, miquelianin, and hyperforin also reversed the glucocorticoid-induced increase in FKBP5 mRNA expression. The effects observed on FKBP5, CREB, GRIK4, VEGF, NET, and ARRB2 are in good correlation with published data, suggesting that this in vitro model could be used to screen the responsiveness of antidepressants under stress conditions.
Keywords: Hypericum perforatum; Clusiaceae; stress; dexamethasone; biomarker; gene expression; FKBP5